ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA BERDASARKAN MINAT BELAJAR MATEMATIS SISWA SMK NEGERI 1 CIHAMPELAS - Siti Robiah; Euis Eti Rohaeti; Eka Senjayawati (Journal on Education, 2019)
This study aims to determine the mathematical communication skills based on learning interests of SMK students. The method in this study uses a correlational method with a quantitative approach. The population in this study was in one of the West Bandung Vocational Schools and the number of samples was 32 students with heterogeneous abilities. The instrument in this study was in the form of a descriptive test of communication skills with six soles and non tests in the form of a learning motivation scale consisting of 20 statement scales. The results of this study obtained that mathematical communication skills based on interest in learning had a positive effect of 30.5%. While 69.5% is influenced other than the students' interest in learning.